Authenticity of liberal feminism in Namita Gokhale’s texts - Priyadharshini, P.; Mohan, S.; Hariharasudan, A.; Sangeetha, J. (Linguistics and Culture Review, 2021)
Liberal feminism abbreviates women’s right and their empowerment. The aim of this study highlights liberal feminism in Namita Gokhale’s works The Book of Shadows (2001), Priya: In Incredible Indyaa (2011) and Things to leave Behind (2016). The features of liberal feminism exhibit the women protagonists’ grief and exertion to attain their goal and their responsibilities. Namita Gokhale is a multifarious writer, and her popular works are The Book of Shadows (2001), Priya: In Incredible Indyaa (2011) and Things to leave Behind (2016). Indian Fiction in general as well as in Indian English Fiction, both original and in translation (Gupta, 2020). The selected works have the issues of liberal feminism ideas that reflect throughout her writing. In Namita Gokhale’s works, the major protagonists that represent liberal feminist attributes are Rachita, Priya and Tilottama. Each character has the reflection of liberal feminist ideas through their life. The notable thinkers of liberal feminism are John Stuart Mill, Mary Wollstonecraft, Betty Friedan, Rosemarie Tong, Susan Moller Okin, Martha Nussbaum and Zillah Eisenstein.